Web: level 5 - Wyndham J. John (Penguin Readers)
Contemporary / British English (Available April 2008) The island of Tanakuatua seems like heaven to the forty people who go there to create a new society. But soon they start to die in a horrible way. Something strange is in the forest. Two of the group decide to fight!